Comparison of three transposons for the generation of highly productive recombinant CHO cell pools and cell lines. Issue 6 (9th December 2015) - Balasubramanian, Sowmya; Rajendra, Yashas; Baldi, Lucia; Hacker, David L.; Wurm, Florian M.
ABSTRACT: Several naturally occurring vertebrate transposable elements have been genetically modified to enable the transposition of recombinant genes in mammalian cells. We compared three transposons—piggyBac, Tol2, and Sleeping Beauty—for their ability to generate cell pools (polyclonal cultures of recombinant cells) and clonal cell lines for the large‐scale production of recombinant proteins using Chinese hamster ovary cells (CHO‐DG44) as the host. Transfection with each of the dual‐vector transposon systems resulted in cell pools with volumetric yields of tumor necrosis factor receptor‐Fc fusion protein (TNFR:Fc) that were about ninefold higher than those from cell pools generated by conventional plasmid transfection. On average, the cell pools had 10–12 integrated copies of the transgene per cell. In the absence of selection, the volumetric productivity of the cell pools decreased by 50% over a 2‐month cultivation period and then remained constant. The average volumetric TNFR:Fc productivity of clonal cell lines recovered from cell pools was about 25 times higher than that of cell lines generated by conventional transfection. In 14‐day fed‐batch cultures, TNFR:Fc levels up to 900 mg/L were obtained from polyclonal cell pools and up to 1.5 g/L from clonal cell lines using any of the three transposons. Biotechnol. Bioeng. 2016;113: 1234–1243. © 2015 Wiley Periodicals, Inc. Abstract : PiggyBac, Tol2, and Sleeping Beauty transposons were used for the rapid generation of polyclonal cell pools and clonal cell lines expressing up to 900 mg/L and 1.5 g/L of a recombinant Fc‐fusion protein, respectively, from Chinese hamster ovary cells in 14‐day fed‐batch cultures. On average, recombinant cells resulting from transposon‐mediated DNA delivery had lower levels of the integrated transgene but higher levels of transgene mRNA accumulation than did recombinant cells generated by conventional plasmid transfection.